Pelatihan Penggunaan Aplikasi E-Tilang pada Kantor Kejaksaan Negeri Ternate - Rachmat Saleh Sukur; Junaidi Sabtu; Akil Thalib (Jurnal Pengabdian Pada Masyarakat, 2021)
TRAINING ON THE USE OF THE E-TILANG APPLICATION AT THE TERNATE DISTRICT ATTORNEY’S OFFICE. The Covid-19 outbreak has an impact to remote areas, the impact can be felt from the community life sector. Judging from this impact, Kejaksaan Agung RI has not stopped initiating and producing innovations, especially in the field of technology, one example is the e-ticket application which is integrated with the Police, Courts and BRI, this application can help officers in community service especially traffic violators without having to make physical contact so as to reduce the spread of covid-19. However, the demand for having human resources (SDM) is also very calculated. With the E-Tilang Application, which from the Attorney General’s Office of the Republic of Indonesia is very helpful for ticketing officers in each region, in helping what is meant is the work of employees, especially ticketing officers, which were previously done conventionally, public services are quickly resolved, but what often becomes an obstacle is resources. human resources, so that with the Community Service Activities carried out, namely training on the use of the E-Tilang application, it can help that human resources, namely ticketing officers, have increased understanding.